2004
DOI: 10.1089/scd.2004.13.571
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic Peripheral Blood Stem Cell Transplantation Using Reduced Intensity Versus Myeloablative Conditioning Regimens for the Treatment of Leukemia

Abstract: Reduced intensity conditioning (RIC) have allowed the application of transplantation to older patients and to patients with underlying medical problems. Between October, 1999, and June, 2003, 61 patients with acute leukemia or chronic myeloid leukemia received allogeneic peripheral blood hematopoietic stem cell transplantation (HSCT) from HLA-identical siblings. Thirty-four were conditioned with myeloablative protocols and twenty-seven with RIC regimens. The patients in the myeloablative group were younger (29… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Following allogeneic HSCT for malignancies, only a few retrospective studies have reported on engraftment interval which generally report earlier WBC and/or platelet recovery using reduced intensity regimens compared to conventional myeloablative protocols. 53,54 In summary, our retrospective study indicates the mobilization of PBSC may be performed safely without significant risk of disease exacerbation using cyclophosphamide and G-CSF mobilization but that astute and close observation and prophylaxis for infectious complica-tions is prudent with immune-mediate diseases. Circulating post-mobilization PB CD34 þ cell numbers vary between autoimmune diseases.…”
Section: Discussionmentioning
confidence: 85%
“…Following allogeneic HSCT for malignancies, only a few retrospective studies have reported on engraftment interval which generally report earlier WBC and/or platelet recovery using reduced intensity regimens compared to conventional myeloablative protocols. 53,54 In summary, our retrospective study indicates the mobilization of PBSC may be performed safely without significant risk of disease exacerbation using cyclophosphamide and G-CSF mobilization but that astute and close observation and prophylaxis for infectious complica-tions is prudent with immune-mediate diseases. Circulating post-mobilization PB CD34 þ cell numbers vary between autoimmune diseases.…”
Section: Discussionmentioning
confidence: 85%
“…One major reason for this is probably that the time to engraftment is not necessarily equivalent to the duration of neutropenia. Some patients undergoing RIC do not reach an absolute neutrophil count of <0.5 × 10 9 /L until after stem cell infusion, and some of these patients never become profoundly neutropenic, i.e., never have a count of <0.1 × 10 9 /L . Another possible explanation is that the time to engraftment is related to stem cell source and human leukocyte antigen mismatch, making it difficult to separate these factors in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…However, some investigators have reported similar cumulative NRM incidence rates (4, 6). We detected no differences in the NRM incidence rates between the groups in this study (47% vs. 56%), although our study involved a somewhat higher incidence rate than was reported in previous studies.…”
Section: Discussionmentioning
confidence: 87%
“…Some investigators have reported lower acute GVHD incidence rates in cases of reduced intensity transplantation (21), while contradictory results also exist (3, 5, 6). The diversity of conditioning regimens, stem cell sources, and GVHD prophylaxis protocols in reduced intensity transplantation might be one reason for this discrepancy.…”
Section: Discussionmentioning
confidence: 99%